A comparative analysis of stability measures between Islamic and conventional banks in selected MENA countries during 1999 to 2015 - Abdul Karim, Norzitah; Syed Jaafar Alhabshi, Syed Musa; Kassim, Salina; Haron, Razali (2016)
The present study, grounded in theory of financial intermediation, provides new empirical evidence on comparison of bank stability measures between Islamic and conventional banks in the MENA region. Specifically, 77 commercial banks and 54 Islamic banks from Bahrain, United Arab Emirates, Kuwait, Qatar, Saudi Arabia and Egypt are considered focusing on the sample period of 1999-2015. The study adopts z-score as a measure of bank stability, while an independent two samples t-test with unequal variance was used to test the significance of the differences between the bank stability of the two banking models, namely Islamic and conventional banks. The sample period is further divided into three sub-periods, namely, before the global financial crisis (1999-2006), during the global financial crisis (2007-2009) and after the global financial crisis (2010-2015) so as to gain more detail findings on the impact of the global financial crisis on the banks’ stability. Findings of this study contribute towards extending the theory of financial intermediation through empirical works of stability of different banking models namely Islamic and conventional banks.